Step 4: Finding.your + C. Now that we have found our general solution and the "g(y)". we can finish up the problem by finding the "+ C". Given the following differential equation [6x? - y + 3] dx + [3y2 - x - 2] dy = 0 Which has an "E" and "g(y)" of F = 2x3 - yx + 3x + g (y) and 8(y) = y3 - 2y + C This gives us a general solution of 2x3 - yx + 3x + y3 - 2y = k Think of the "k" as the "+ C", we just moved it to the other side. Use the initial condition " y(0) = 8 " to find "k" and thus the specific solution for the problem. (A) 2x3 - yx + 3x + y3 - 2y = - 4 B) 2x3 - yx + 3x + y3 - 2y = 1048 2x - yx + 3x + y - 2y = 496 D 2x3 - yx + 3x + y3 - 2y = 8 E 2x3 - yx + 3x + y - 2y = 0

Advanced Engineering Mathematics
10th Edition
ISBN:9780470458365
Author:Erwin Kreyszig
Publisher:Erwin Kreyszig
Chapter2: Second-order Linear Odes
Section: Chapter Questions
Problem 1RQ
icon
Related questions
Question

q9

Step 4: Finding.your + C.
Now that we have found our general solution and the "g(y)". we can finish up the problem by finding the "+ C".
Given the following differential equation
[6x? - y + 3] dx + [3y? - x - 2] dy = 0
Which has an "F" and "g(y)" of
F = 2x3 - yx + 3x + g (y) and 8(y) = y3 - 2y + C
%3D
This gives us a general solution of
2x3 - yx + 3x + y3 - 2y = k
Think of the "k" as the "+ C", we just moved it to the other side. Use the initial condition " y(0) = 8 " to find "k" and thus the specific
solution for the problem.
(A)
2x3 - yx + 3x + y3 - 2y = - 4
B)
2x3 - ух + 3х + уз - 2у
= 1048
2x - yx + 3x + y - 2y = 496
D
2x3 - yx + 3x + y3 - 2y = 8
E
2x - yx + 3x + y - 2y = 0
Transcribed Image Text:Step 4: Finding.your + C. Now that we have found our general solution and the "g(y)". we can finish up the problem by finding the "+ C". Given the following differential equation [6x? - y + 3] dx + [3y? - x - 2] dy = 0 Which has an "F" and "g(y)" of F = 2x3 - yx + 3x + g (y) and 8(y) = y3 - 2y + C %3D This gives us a general solution of 2x3 - yx + 3x + y3 - 2y = k Think of the "k" as the "+ C", we just moved it to the other side. Use the initial condition " y(0) = 8 " to find "k" and thus the specific solution for the problem. (A) 2x3 - yx + 3x + y3 - 2y = - 4 B) 2x3 - ух + 3х + уз - 2у = 1048 2x - yx + 3x + y - 2y = 496 D 2x3 - yx + 3x + y3 - 2y = 8 E 2x - yx + 3x + y - 2y = 0
Expert Solution
trending now

Trending now

This is a popular solution!

steps

Step by step

Solved in 3 steps with 2 images

Blurred answer
Recommended textbooks for you
Advanced Engineering Mathematics
Advanced Engineering Mathematics
Advanced Math
ISBN:
9780470458365
Author:
Erwin Kreyszig
Publisher:
Wiley, John & Sons, Incorporated
Numerical Methods for Engineers
Numerical Methods for Engineers
Advanced Math
ISBN:
9780073397924
Author:
Steven C. Chapra Dr., Raymond P. Canale
Publisher:
McGraw-Hill Education
Introductory Mathematics for Engineering Applicat…
Introductory Mathematics for Engineering Applicat…
Advanced Math
ISBN:
9781118141809
Author:
Nathan Klingbeil
Publisher:
WILEY
Mathematics For Machine Technology
Mathematics For Machine Technology
Advanced Math
ISBN:
9781337798310
Author:
Peterson, John.
Publisher:
Cengage Learning,
Basic Technical Mathematics
Basic Technical Mathematics
Advanced Math
ISBN:
9780134437705
Author:
Washington
Publisher:
PEARSON
Topology
Topology
Advanced Math
ISBN:
9780134689517
Author:
Munkres, James R.
Publisher:
Pearson,